Manfaat Algoritma Pemrograman Dalam Penerapan Aplikasi Pemecah Masalah Persoalan Matematika Geogebra - Yuan Amelia Tri Ananda; Yahfizham (CV. ITTC INDONESIA, 2023)
Everything on a computer, especially in the use of applications or programs, must utilize programming algorithms. Programming algorithms are not only useful in simple computer programs but also utilize high-level calculations. One of the uses of programming algorithms is to be used in the application of a problem-solving application for mathematical problems such as geogebra. This paper aims to find out how and what are the benefits of programming algorithms in the application of problem solving applications for geography math problems. There is this paper the author uses a literature study method and a qualitative method in the form of techniques. The author also describes the benefits of the advantages of programming algorithms in the application of problem solving applications for math problems such as geogebra.